Classification and neuroimaging of ependymal tumors - Mu, Weiya; Dahmoush, Hisham (Frontiers in Pediatrics, 2023)
Ependymal tumors arise from the ependymal cell remnants of the cerebral ventricles, the central canal of the spinal cord, or the filum terminale or conus medullaris, although most pediatric supratentorial ependymomas do not exhibit clear communication or abutment of the ventricles. In this article, we discuss the classification, imaging characteristics, and clinical settings of these tumors. The WHO 2021 classification system has categorized ependymal tumors based on histopathologic and molecular features and location, in which they are grouped as supratentorial, posterior fossa (PF), and spinal. The supratentorial tumors are defined by either the ZFTA (formerly RELA) fusion or the YAP1 fusion. Posterior fossa tumors are divided into group A and group B based on methylation. On imaging, supratentorial and infratentorial ependymomas may arise from the ventricles and commonly contain calcifications and cystic components, with variable hemorrhage and heterogeneous enhancement. Spinal ependymomas are defined by MYCN amplification. These tumors are less commonly calcified and may present with the “cap sign,” with T2 hypointensity due to hemosiderin deposition. Myxopapillary ependymoma and subependymoma remain tumor subtypes, with no change related to molecular classification as this does not provide additional clinical utility. Myxopapillary ependymomas are intradural and extramedullary tumors at the filum terminale and/or conus medullaris and may also present the cap sign. Subependymomas are homogeneous when small and may be heterogeneous and contain calcifications when larger. These tumors typically do not demonstrate enhancement. Clinical presentation and prognosis vary depending on tumor location and type. Knowledge of the updated WHO classification of the central nervous system in conjunction with imaging features is critical for accurate diagnosis and treatment.